2022
DOI: 10.3389/fpls.2022.933849
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Reveals the Differences Between Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd.

Abstract: Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd. are two varieties of Bupleuri Radix in Chinese Pharmacopoeia 2020. The clinical efficacy of the two bupleurum species is different. The difference in clinical efficacy is closely related to the composition of plant metabolites. In order to analyze the difference in metabolites, we used liquid chromatography coupled with mass spectrometry (LC-MS) for untargeted metabolome and gas chromatography coupled with mass spectrometry (GC-MS) for widely targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Recently, Qu et al extracted and compared the metabolite compositions of different parts of wild North and South RB grown in suburban mountainous areas. They found that there were significant differences in metabolites between different tissues and speculated that the great differences in the saikosaponin content and metabolic networks were closely related to the clinical efficacy of Radix Bupleuri [6]. These results offer a highly valuable reference for guiding the clinical use of Radix Bupleuri.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Qu et al extracted and compared the metabolite compositions of different parts of wild North and South RB grown in suburban mountainous areas. They found that there were significant differences in metabolites between different tissues and speculated that the great differences in the saikosaponin content and metabolic networks were closely related to the clinical efficacy of Radix Bupleuri [6]. These results offer a highly valuable reference for guiding the clinical use of Radix Bupleuri.…”
Section: Introductionmentioning
confidence: 99%
“…They also differ in their pharmacological ac tivities and functions, as documented in the classics of Chinese medicine, Materia Medic Synopsis and Materia Medica Compendium. North RB is typically used to treat typhoid feve while South RB is mainly used to clear liver heat [6]. However, in most clinical practice both are confused and used without distinction as Radix Bupleuri [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, B. scorzonerifolium root has been recorded in the Chinese, British and European Pharmacopoeias as an official medicine, and it is used for the treatment of catching a cold, fever, inflammation and hepatitis (Pharmacopoeia, E.C.O.C, 2020;Sun et al, 2020). Up to now, phytochemical studies reported that B. scorzonerifolium root contained several kinds of natural constituents, such as triterpenoid saponins, volatile oils, flavonoids, polysaccharides, lignans and so on (Jiang et al, 2020;Qu et al, 2022). In China, B. scorzonerifolium is known as "Xiang Chaihu", because it contains a high content of volatile oil giving it a strong odor.…”
Section: Introductionmentioning
confidence: 99%
“…In the long process of evolution, a large number of metabolites with different biological functions have been synthesized by plants in response to stimulation by a changeable environment [ 14 ]. Plants have a wide range of habitats and are usually exposed to a variety of abiotic stresses; thus, they differ in their morphology and metabolism, resulting in different adaptations to and ecotypes within an environment [ 15 , 16 ]. Plants contain primary and secondary metabolites, and secondary metabolites are involved in the environmental response of resistance to abiotic and biotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Plants contain primary and secondary metabolites, and secondary metabolites are involved in the environmental response of resistance to abiotic and biotic stress. Some substances can improve the stress resistance of plants [ 16 ]. Flavonoids are an important family of secondary metabolites involved in plant development and defense, with a variety of functions such as antioxidant and antibacterial activity as well as free radical scavenging, and they are also believed to enhance tolerance to abiotic stresses [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%